Tinjauan Hukum dalam Menangani Kasus Sengketa Medis antara Tenaga Medis pada Sistem Peradilan - Rusdi, Adi Muhammad; Dhea Salsabila, Vivian; Hasudungan Tampubolon, Boris; Ardhianysah Pandiangan, Eko (Green Publisher Indonesia, 2025)
The legal relationship between doctors and patients, known as a therapeutic transaction, forms the basis of medical services. This study aims to examine the dispute resolution mechanisms between healthcare professionals and patients, both within and outside of hospitals. The approach used is normative juridical, focusing on healthcare services where outcomes are uncertain, yet medical professionals are obligated to inform patients or their families of any potential medical risks prior to performing any procedures. This refers to the provisions of Law No. 29 of 2004 concerning Medical Practice, which requires doctors to obtain informed consent from patients after providing a thorough and clear explanation. This explanation should cover the diagnosis, the medical procedures to be undertaken, the purpose of the procedure, alternative treatments along with their associated risks, potential complications, and the prognosis following the procedure. In addition to resolving disputes through litigation in court, mediation as a form of non-litigation dispute resolution is also regulated under Article 29 of Law No. 36 of 2009 on Health. This article emphasizes that medical disputes should preferably be settled outside the court through mediation conducted by a mediator mutually agreed upon by both parties involved in the dispute.